Enhancing Diversity and Inclusion in Clinical Trials. Issue 3 (11th January 2023) - Corneli, Amy; Hanlen‐Rosado, Emily; McKenna, Kevin; Araojo, Richardae; Corbett, Dawn; Vasisht, Kaveeta; Siddiqi, Bernadette; Johnson, Tesheia; Clark, Luther T.; Calvert, Sara B.
Abstract : Women and people from most racial and ethnic groups in the United States have historically been under‐represented in clinical trials of investigational medical products. Inadequate representation of these groups may lead to an incomplete understanding of the safety and efficacy of new drugs, devices, biologics, and vaccines, and limit the generalizability of trial findings. As a result, new medical products may not be beneficial to all people who need them, and existing inequities in outcomes among various population groups may remain unchanged or worsen, or new disparities may arise. Although much work has focused on study‐level strategies, research organizations must make systemic changes to how clinical trials are envisioned and implemented to achieve sustainable support for diversity and inclusion in clinical trials. The Clinical Trials Transformation Initiative (CTTI) conducted interviews with leaders at institutions that conduct clinical trials to explore perspectives on organizational‐level practices that promote diversity and inclusion in clinical trials. Leaders described motivations, such as an ethical and moral imperative; organizational practices, such as staff investment and resource allocation; perceived return on investments, such as better science; and deterrents, such as cost and time. The CTTI also convened an expert meeting to discuss the interview findings and provide guidance. We present the interview findings and expert guidance in a framework that describes four key areas—commitment, partnerships, accountability, and resources—on sustaining organizational‐level approaches for improving diversity and inclusion in clinical trials, with the ultimate goal of advancing health equity. Institutions who conduct and support clinical trials should implement organizational‐level approaches to improve equitable access and diverse patient participation in clinical trials.